Essential Metal Levels in Cosmetologists, Heavy Cosmetic Users and Cosmetic-Naive Individuals in Benin City, South-South, Nigeria - Igharo, O. G.; Okungbowa, M. A.; Igharo, E. L.; Ezegbogu , O. M. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
A growing number of research on the subject of cosmetics have been aimed at examining the toxicological and carcinogenic consequences of cosmetic use. This study aimed at evaluating the plasma levels of select biologically essential metals in cosmetologists, heavy cosmetic users, and in age-matched non-users of cosmetics (negative control group) in Benin City, Nigeria. From the blood samples obtained, levels of Iron, Zinc, Copper, Selenium, and Cobalt were determined using inductively coupled plasma mass spectrometry. Exposure frequency of ?36h per week, coupled with inadequate use of personal protective equipment was observed among the cosmetologists. Though Selenium and Cobalt levels were significantly lower in cosmetologists, their levels were similar in non-users of cosmetics (NUC) and heavy cosmetic users (HCU). Levels of Zinc and Copper were similar in HCU and NCU but significantly higher when compared with cosmetologists. Iron levels varied significantly across the groups (NUC > HCU > cosmetologists). This study suggests that prolonged occupational and/or lifestyle exposure to cosmetic-borne chemicals may lead to a depression in the systemic levels of biologically essential metals such as Iron, Zinc, and Copper in cosmetic exposed individuals or users, and this may predispose to pathologic states associated with essential metal deficiency.